Quantum dots and nanowires for optoelectronic device applications - Gao, Q; Kim, Y; Joyce, H; Lever, P; Mokkapati, S; Buda, M; Tan, H; Jagadish, C (2006)
InGaAs quantum dots (QDs) and nanowires have been grown on GaAs by metal-organic chemical vapour deposition on GaAs (100) and (111)B substrates, respectively. InGaAs QD lasers were fabricated and characterised. Results show ground-state lasing at about 1150 nm in devices with lengths greater than 2.5 mm. We also observed a strong influence of nanowire density on nanowire height specific to nanowires with high indium composition. This dependency was attributed to the large difference of diffusion length on (111)B surfaces between In and Ga reaction species, with In being the more mobile species. Selective area epitaxy for applications in quantum-dot optoelectronic device integration is also discussed in this paper. ©2006 IEEE.